(untitled) - Vicary, Tim (Oxford, 1997)
When a large plane is hijacked, the Prime Minister looks at the list of passengers and suddenly becomes very frightened. There is a name on the list that the Prime Minister knows vere well - too well. There is someone on that plane who will soon be dead - if the hijackers can find out who he is! And there isn't much time. One man lies dead on the runway. In a few minutes the hijackers will use their guns again. And the prime Minister knows who they are going to kill.
Keywords: English fiction,English literature; 20th century